Manipulation of 2D and 3D Magnetic Solitons Under the Influence of DMI Gradients - Rayan Moukhader; Davi Rodrigues; Eleonora Raimondo; Vito Puliafito; Bruno Azzerboni; Mario Carpentieri; Abbass Hamadeh; Giovanni Finocchio; Riccardo Tomasello (IEEE Open Journal of Nanotechnology)
Magnetic solitons hold great promise for token-based computing applications due to their intrinsic properties, including small size, topological stability, ultra-low power manipulation, and potentially ultra-fast operation. In particular, they have been proposed as reliable memory units that enable the execution of various logic tasks with in-situ memory. A critical challenge remains the identification of optimal soliton and efficient manipulation techniques. Previous research has primarily focused on the manipulation of two-dimensional solitons, such as skyrmions, domain walls, and vortices, by applied currents. The discovery of novel methods to control magnetic parameters, such as the interfacial Dzyaloshinskii-Moriya interaction, through strain, temperature gradients, and applied voltages offers new avenues for energetically efficient manipulation of magnetic structures. In this work, we present a comprehensive study using numerical and analytical methods to investigate the stability and motion of various magnetic textures under the influence of DMI gradients. Our results show that Néel and Bloch-type skyrmions, as well as radial vortices, exhibit motion characterized by finite skyrmion Hall angles, while circular vortices undergo expulsion dynamics. This study provides a deeper and crucial understanding of the stability and gradient-driven dynamics of magnetic solitons, paving the way for the design of scalable spintronics token-based computing devices.